Increases in temperature and nutrient availability positively affect methane‐cycling microorganisms in Arctic thermokarst lake sediments - Anniek E. E. de Jong; Michiel H. in ’t Zandt; Ove H. Meisel; Mike S. M. Jetten; Joshua F. Dean; Olivia Rasigraf; Cornelia U. Welte (Environmental Microbiology, 2018)
Summary Arctic permafrost soils store large amounts of organic matter that is sensitive to temperature increases and subsequent microbial degradation to methane (CH 4 ) and carbon dioxide (CO 2 ). Here, we studied methanogenic and methanotrophic activity and community composition in thermokarst lake sediments from Utqiag˙vik (formerly Barrow), Alaska. This experiment was carried out under in situ temperature conditions (4°C) and the IPCC 2013 Arctic climate change scenario (10°C) after addition of methanogenic and methanotrophic substrates for nearly a year. Trimethylamine (TMA) amendment with warming showed highest maximum CH 4 production rates, being 30% higher at 10°C than at 4°C. Maximum methanotrophic rates increased by up to 57% at 10°C compared to 4°C. 16S rRNA gene sequencing indicated high relative abundance of Methanosarcinaceae in TMA amended incubations, and for methanotrophic incubations Methylococcaeae were highly enriched. Anaerobic methanotrophic activity with nitrite or nitrate as electron acceptor was not detected. This study indicates that the methane cycling microbial community can adapt to temperature increases and that their activity is highly dependent on substrate availability.

Genes Relocated Between Drosophila Chromosome Arms Evolve Under Relaxed Selective Constraints Relative to Non-Relocated Genes - Margaret L. I. Hart; Ban L. Vu; Quinten Bolden; Keith T. Chen; Casey L. Oakes; Lejla Zoronjic; Richard P. Meisel (Journal of Molecular Evolution, 2018)

Calcium Microcrystal Formation in Recurrent Herniation Patients After Autologous Disc Cell Transplantation - S. Schwan; C. Ludtka; A. Friedmann; T. Mendel; H. J. Meisel; A. Heilmann; I. Kaden; F. Goehre (Tissue Engineering and Regenerative Medicine, 2017)

GGOS-D: homogeneous reprocessing and rigorous combination of space geodetic observations - M. Rothacher; D. Angermann; T. Artz; W. Bosch; H. Drewes; M. Gerstl; R. Kelm; D. König; R. König; B. Meisel; H. Müller; A. Nothnagel; et al. (Journal of Geodesy, 2011)

Brain antigens in functionally distinct antigen-presenting cell populations in cervical lymph nodes in MS and EAE - Marloes van Zwam; Ruth Huizinga; Marie-José Melief; Annet F. Wierenga-Wolf; Marjan van Meurs; Jane S. Voerman; Knut P. H. Biber; Hendrikus W. G. M. Boddeke; Uta E. Höpken; Christian Meisel; Andreas Meisel; Ingo Bechmann; et al. (Journal of Molecular Medicine, 2009)

Diverse contributing sources to chromitite petrogenesis in the Shebenik Ophiolitic Complex, Albania: evidence from new PGE- and Os-isotope data - H. Kocks; F. Melcher; T. Meisel; K.-P. Burgath (Mineralogy and Petrology, 2007)

Possible role of MDR1 two-locus genotypes for young-age onset ulcerative colitis but not Crohn’s disease - T. Fiedler; C. Büning; W. Reuter; G. Pitre; E. Gentz; HH. Schmidt; J. Büttner; J. Ockenga; T. Gerloff; C. Meisel; H. Lochs; I. Roots; et al. (European Journal of Clinical Pharmacology, 2007)

Relics of eclogite facies metamorphism in the Austroalpine basement, Hochgrssen (Speik complex), Austria - G. Hoinkes; S. W. Faryad; J. Puhl; W. Frank; F. Melcher; T. Meisel (Mineralogy and Petrology, 2002)

Polymorphism of the N -acetyltransferase ( NAT2 ), smoking and the potential risk of periodontal disease - P. Meisel; Ramona Timm; H. Sawaf; Jutta Fanghänel; Werner Siegmund; T. Kocher (Archives of Toxicology, 2000)